Staff Callewaert, Martin Munk, Morten Nørholm og Karin Anna Petersen, Pierre Bourdieu. Centrale tekster inden for sociologi og kulturteori, København: Akademisk Forlag, 1994, 176 s. - Mortensen, Niels (Politica, 1996)
-